Letter - Winstanley, E.
030-0141-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. Our reference EXPORT ST/HP. 1179 Your reference 25th June, 1938. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, We beg to make further reference to the order you recently placed in respect of Dried Cod and Soap, and now have pleasure in informing you that shipment has duly been effected by s.s. C.W.S. PROGRESS from Garston to Rouen, on Thursday last, the 23rd instant. The Bill of Lading and invoice for customs purposes has been sent forward to our Rouen Depot, who inform us that they have made arrangements for the goods to be despatched to Spain via Cerbere, under bond. The s.s. "C.W.S. PROGRESS" is due to unload at Rouen on Monday, the 27th instant, and we anticipate, therefore, that the goods should be in the hands of consignee towards the end of this month or beginning of July. Our invoice covering the goods and freight will follow on Monday. Meanwhile, we remain, Yours faithfully, E. Winstanley Export Department. 292/946/30/141